2022
DOI: 10.1002/cncr.34506
|View full text |Cite
|
Sign up to set email alerts
|

Complete tumor necrosis after neoadjuvant chemotherapy defines good responders in patients with Ewing sarcoma

Abstract: Background: Survival in patients who have Ewing sarcoma is correlated with postchemotherapy response (tumor necrosis). This treatment response has been categorized as the response rate, similar to what has been used in osteosarcoma.There is controversy regarding whether this is appropriate or whether it should be a 60 - Cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Not surprisingly, data on the tumor necrosis percentage in STS in relation to clinical outcomes are contradictory [18,20]. The data obtained in this study support the conclusion that, in contrast to bone sarcomas, tumor necrosis has no clear prognostic value in MFS [19,34].…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Not surprisingly, data on the tumor necrosis percentage in STS in relation to clinical outcomes are contradictory [18,20]. The data obtained in this study support the conclusion that, in contrast to bone sarcomas, tumor necrosis has no clear prognostic value in MFS [19,34].…”
Section: Discussionsupporting
confidence: 43%
“…Recently, neoadjuvant radiotherapy has been replacing adjuvant radiotherapy as the preferred treatment modality, as it enables more accurate definition of the treatment field and thus limits damage to adjacent structures [14,15]. The role of nRT has been investigated in different histological subtypes of STS, but not in MFS, where positive surgical margins and high tumor necrosis have been identified as predictors for worse clinical outcome [16][17][18][19][20][21]. A high percentage of tumor necrosis, histologically assessed, after nRT is the most commonly used surrogate marker for treatment response; however, this has not been validated in STS and small studies present conflicting data [18][19][20]22].…”
Section: Introductionmentioning
confidence: 99%
“…13 Our analysis also supports previous data suggesting that categorizing tumors as NVT versus AVT may be a better discriminator of outcome. 14,15 The outstanding outcomes for patients with NVT who received ICC should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Boston (Massachusetts, USA) included 427 patients who had Ewing’s sarcoma or family lesions and underwent preoperative chemotherapy followed by surgery at one of ten institutions. 1 After controlling for clinical factors identified in bivariate analysis (including age, tumour volume, location, surgical margins, metastatic disease at presentation, and preoperative radiotherapy), patients who had a complete (100%) tumour response to chemotherapy had increased overall survival, recurrence-free survival, metastasis-free survival, and event-free survival when compared with patients who had a partial response (0% to 99%). The authors concluded that complete tumour necrosis should be the index parameter to grade response to treatment as satisfactory in patients with Ewing’s sarcoma.…”
Section: Complete Tumour Necrosis After Neoadjuvant Chemotherapy Defi...mentioning
confidence: 97%